GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 8 species occurrences available in GBIF matching the query: TaxonKey: Atelopus flavescens Duméril and Bibron, 1841 HasGeospatialIssue: false HasCoordinate: true. The dataset includes 8 records from 4 constituent datasets: 1 records from NMNH occurrence DwC-A. 4 records from LACM Vertebrate Collection. 1 records from RBINS collections. 2 records from Borror Lab of Bioacoustics (BLB), Ohio State University.
Keywords: GBIF; biodiversity; species occurrences